Perbandingan Sistem Perizinan Badan Hukum di Indonesia dan Negara ASEAN - Yacob Ferdian Martono; Muhammad Akbar P. G.; Yohannes Boy Panggo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research compares legal entity licensing systems in Indonesia and other ASEAN member states in response to the growing need for regulatory harmonization and improved ease of doing business within the region, particularly after ASEAN economic integration accelerated cross border investment activities. Differences in administrative requirements, processing duration, and the level of digitalization among countries often create barriers for business expansion, making a comparative assessment essential to understand Indonesia’s current position and identify potential improvements. The main objective of this study is to analyze the characteristics of Indonesia’s legal entity licensing system by comparing it with ASEAN countries that have adopted more advanced administrative reforms, while also evaluating how regional best practices can inform national policy development. The study applies a qualitative method using a descriptive comparative approach, focusing on regulatory frameworks, institutional arrangements, levels of digital integration, and indicators related to ease of doing business. The results show that although Indonesia has introduced electronic licensing systems, several challenges remain, including uneven implementation, overlapping institutional authority, and variations in service quality across regions. In contrast, countries such as Singapore and Malaysia have established licensing systems that are more integrated, transparent, and oriented toward user needs, resulting in greater legal certainty for investors. These findings highlight the importance of strengthening regulatory alignment, improving digital system integration, and enhancing institutional capacity so that Indonesia can reach efficiency levels comparable to its regional counterparts and contribute to a more competitive and sustainable ASEAN business environment.